Jawabanmu

Jawaban paling cerdas!
2014-05-20T09:59:01+07:00
\sqrt{ 3x^{2}+1 } -1 \\ = ( 3x^{2}+1) ^{ \frac{1}{2} }-1 \\ \\ y = u ^{ \frac{1}{2} }-1 \\ u = 3x^{2}+1 \\ \\ \frac{dy}{du} = \frac{1}{2} u^{ -\frac{1}{2} } \\ \frac{du}{dx}=6x \\ \\ \frac{dy}{dx} = \frac{dy}{du}.\frac{du}{dx} \\ \frac{dy}{dx} =\frac{1}{2} u^{ -\frac{1}{2}}.6x = \frac{1}{2} (3x^{2}+1)^{ -\frac{1}{2}}.6x \\ \frac{dy}{dx} = \frac{3x}{ \sqrt{3x^{2}+1} }
Komentar sudah dihapus
interval -2
Komentar sudah dihapus
Komentar sudah dihapus
hehe samasama :)